The availability of treaty relief for secondary transfer pricing adjustments taking the form of a deemed distribution of an asset in specie in South Africa - Strauss, Carien (Department of Finance and Tax, 2017)
The number of MNEs have increased substantially in recent years, putting a strain on international tax rules which have not developed at the same pace. Many of these MNEs have kept their tax bill at a minimum by shifting profits to low tax jurisdictions by using transfer prices that do not accord with economic reality. In response hereto, many tax jurisdictions have implemented domestic anti-avoidance legislation to assist tax authorities in curbing tax avoidance resulting from the manipulation of transfer prices. SA is an example of such a country. These anti-avoidance provisions typically involve a primary and secondary adjustment. The primary adjustment requires that an adjustment be made to the transfer price used by the MNE in the event that the said price does not reflect an arm's length price. The secondary adjustment concerns itself with making the actual allocation of funds consistent with the primary adjustment by deeming there to be another transaction, i.e. the secondary transaction. In SA, this secondary adjustment takes the form of a deemed distribution of an asset in specie in the case of residents who are companies. As such, this secondary transaction (i.e. the deemed dividend) is subject to Dividends Tax in SA levied at the domestic rate. This study considered whether such a deemed dividend will qualify for treaty relief in the form of the reduced rate provided for by Article 10 of the OECD MTC and UN MTC. In making this analysis, three main issues where specifically considered, namely (i) whether the SA company paying the Dividends Tax will have access to treaty relief in cases where Dividends Tax is not listed as a covered tax in the relevant tax treaty, (ii) whether a deemed dividend under a secondary adjustment in terms of SA domestic law falls within the dividend definition contained in Article 10.3 of the OECD and UN MTC, and finally (iii) whether the relevant deemed dividend can be regarded as 'paid' for purposes of Article 10.1 and 10.2 of the OECD MTC and UN MTC. It was concluded that the SA Company will not qualify for the reduced rate provided for by tax treaties modelled on the OECD MTC and UN MTC as the deemed dividend does not fall within the ambit of the dividend definition contained in these model treaties. However, some of SA's tax treaties currently in force, deviate from the wording used in these model treaties to such an extent that it brings deemed dividends under a secondary adjustment in SA within the scope of the dividend definition, and in doing so, provides the SA Company with access to the reduced rates provided for in tax treaties. Examples hereof are the tax treaties that SA have concluded with the UK and NZ. Should SA decide to adopt a more 'forgiving' approach towards the availability of relief for secondary adjustments, it is recommended that SA either amend the domestic relief provisions to allow access to such relief, or amend the dividend definition contained in the tax treaties it currently has in force to include deemed dividends in terms of secondary adjustments in SA. The first approach is preferred as it is not always possible and timely to amend tax treaties currently in force.